PERAN POSYANDU DALAM PELAYANAN KESEHATAN MASYARAKAT - Susanti, Erwina (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Elderly health care coverage in Public Health Jalan Gedang as much (81.92%)and the number of elderly as many as 686 people. Visit the elderly who come to posyanduranges from 41-53 people per month in 2016. The health center has two IHC GedangWay consists of IHC Elderly Elderly Serayu Mandiri and Posyandu Elderly Peace. IHChas five cadres and participants 44 people. Elderly Posyandu cadre of Peace has fivepeople, participants lansianya 50 people. IHC Elderly Peace has many achievements thanPosyandu Elderly Serayu Mandiri The study design used in this research is descriptivequalitative method. Informants in this study as many as 10 cadres and 1 officer in chargePosyandu program. The study design used in this research is descriptive qualitativemethod. Knowledge Posyandu Elderly Peace found that IHC Elderly for seniors 60 yearsand older age range and Posyandu Elderly Serayu Mandiri that Posyandu Elderly agerange of 40 years and above. Attitude Posyandu Elderly Peace mostly elderly support andintegrated support Serayu Mandiri attitude. Kader Posyandu Elderly Peace and PosyanduElderly Serayu Mandiri mostly not expect incentives. Kader Posyandu Elderly Peacemostly mentioned five systems the table properly and Posyandu Elderly Serayu Mandirino mention of five tables with the right system. Expected to conduct refresher training orvolunteers to knowledge about Posyandu cadres better, could improve the role in theservice of Posyandu.